Complications of delayed diagnosis and challenges: successfully managed SPTB gene variant hereditary spherocytosis with hepatocellular jaundice—a case report - Sintayehu Mekonnen; Dereje Adefris; Belete Shikuro; Abdi Bati; Daniel Azmeraw; Temesegen Kassa; Eliud Teshome; Hawi Farris (Journal of Medical Case Reports, 2024)
Abstract Background Hereditary spherocytosis is a rare genetic disorder of the red blood cell membrane that is characterized by anemia, jaundice, and splenomegaly; however, in the absence of family history and with unusual clinical presentation, the diagnosis might not be made until later in life. Case presentation Here, we present a challenging case of genetically proven hereditary spherocytosis that involves the SPTB gene in a 23-year-old female patient from Ethiopia who had repeated medical visits for episodic jaundice and hepatosplenomegaly, with unusual features of conjugated hyperbilirubinemia, pancytopenia, normal reticulocyte count, and lack of family history, where the delay in diagnosis led to several complications. The patient was successfully managed with simultaneous splenectomy and cholecystectomy. Conclusion This case underscores the importance of a thorough clinical examination, spending the time to review a case periodically without assuming the initial diagnosis is correct, and maintaining a healthy skepticism of inconsistent data to prevent misdiagnosis and mistreatment. The diagnostic delay highlights the need for increased awareness and familiarity with diagnostic modalities of hereditary spherocytosis among healthcare providers in Ethiopia.